Pemodelan Suspensi Kendaraan Dalam Tinjauan Multi Derajat Kebebasan - Pipit Wahyu Nugroho; Mochamad Muzaki (Polinema Press, Politeknik Negeri Malang, 2021)
The two most important parameters in vehicle vibration are the level of comfort and stability. To get the best value from that parameter, the vehicle suspension system is very important to reduce vibration due to road waves and keep the wheels attached to the road. This paper studied the effect of the type of suspension on the vibration of a one-wheeled vehicle in terms of comfort and stability. The type of suspension is related to the value of the spring stiffness and the damping. While the vehicle is modeled with one wheel in two degrees of freedom. The test is carried out by loading the vehicle including the mass of the vehicle and passengers for each type of suspension, namely soft, medium and hard. Vibration analysis was performed using Matlab Simulink to obtain the acceleration response and deflection response. The vibration response graph shows the comparison of the level of comfort and stability of the vehicle on the road profile modeled in step, impulse and sinusoidal functions. From the simulation results, it is found that the Soft and Medium Suspension can handle vibration very well, especially from the level of response speed for relatively flat roads. Meanwhile, the Hard type of suspension is very good at dampening vibrations for high bumpy roads.